Cover Image. Issue 3 (4th March 2023) - Gur, Ersin; Tiftikcioglu, Yigit Ozer; Ozturk, Kerem
Abstract : The cover image is based on the Research Article Transferring pectoral muscle flap to depleted neck to create a new recipient source for free flaps in head and neck reconstruction by Ersin Gur MD et al., https://doi.org/10.1002/micr.30953 .